Photoexcited toluidine blue inhibits tau aggregation in Alzheimer's disease - Dubey, Tushar; Nalini, Gorantla Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The aggregates of microtubule-associated protein Tau are considered as a major hallmark of Alzheimer's disease. Tau aggregates accumulate intracellularly leading to neuronal toxicity. Numerous approaches have been targeted against Tau protein aggregation, which include application of synthetic and natural compounds. Toluidine blue is a basic dye of phenothiazine family, which on irradiation with a 630 nm light gets converted into a photoexcited form, leading to generation of singlet oxygen species. Methylene blue is the parent compound of toluidine blue, which has been reported to be potent against tauopathy. In the present work, we studied the potency of toluidine blue and photoexcited toluidine blue against Tau aggregation. Biochemical and biophysical analyses using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, ThS fluorescence, circular dichroism spectroscopy, and electron microscopy suggested that toluidine blue inhibited the aggregation of Tau in vitro. The photoexcited toluidine blue potentially dissolved the matured Tau fibrils, which indicated the disaggregation property of toluidine blue. The cell biology studies including the cytotoxicity assay and reactive oxygen species (ROS) production assay suggested toluidine blue to be a biocompatible dye as it reduced ROS levels and cell death. The photoexcited toluidine blue modulates the cytoskeleton network in cells, which was supported by immunofluorescence studies of neuronal cells. The studies in a UAS Tau E14 transgenic Drosophila model suggested that photoexcited toluidine blue was potent to restore the survival and memory deficits of Drosophila. The overall finding of our studies suggested toluidine blue to be a potent molecule in rescuing the Tau-mediated pathology by inhibiting its aggregation, reducing the cell death, and modulating the tubulin levels and behavioral characteristics of Drosophila. Thus, toluidine blue can be addressed as a potent molecule against Alzheimer's disease.

Photodynamic exposure of Rose-Bengal inhibits Tau aggregation and modulates cytoskeletal network in neuronal cells - Dubey, Tushar; Gorantla, Nalini Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The intracellular Tau aggregates are known to be associated with Alzheimer's disease. The inhibition of Tau aggregation is an important strategy for screening of therapeutic molecules in Alzheimer's disease. Several classes of dyes possess a unique property of photo-excitation, which is applied as a therapeutic measure against numerous neurological dysfunctions. Rose Bengal is a Xanthene dye, which has been widely used as a photosensitizer in photodynamic therapy. The aim of this work was to study the protective role of Rose Bengal against Tau aggregation and cytoskeleton modulations. The aggregation inhibition and disaggregation potency of Rose Bengal and photo-excited Rose Bengal were observed by in-vitro fluorescence, circular dichroism, and electron microscopy. Rose Bengal and photo-excited Rose Bengal induce minimal cytotoxicity in neuronal cells. In our studies, we observed that Rose Bengal and photo-excited Rose Bengal modulate the cytoskeleton network of actin and tubulin. The immunofluorescence studies showed the increased filopodia structures after photo-excited Rose Bengal treatment. Furthermore, Rose Bengal treatment increases the connections between the cells. Rose Bengal and photo-excited Rose Bengal treatment-induced actin-rich podosome-like structures associated with cell membranes. The in-vivo studies on UAS E-14 Tau mutant Drosophila suggested that exposure to Rose Bengal and photo-excited Rose Bengal efficiency rescues the behavioural and memory deficit in flies. Thus, the overall results suggest that Rose Bengal could have a therapeutic potency against Tau aggregation.